STUDIES OF UTRICULARIA SPECIES IN WESTERN SARAWAK, MALAYSIA - Umie Naylisa, Mohamad Asmadi; Meekiong, Kalu; Mogeret, Sidi (Forestry Department Peninsular Malaysia, 2023)
Utricularia (Lentibulariaceae) is the second largest genus among the carnivorous plants that are also known as the bladderworts. This genus is cosmopolitan and it can be found in a variety of habitats, including subarctic environments, tropical rainforests, desert oases, and maritime islands. Generally, Utricularia has a few habits that they could survive in such as in freshwater aquatic, semi-aquatic, terrestrial, and lithophytic conditions. The genus can be found in Malesia, with ca. 30 species. So far, 14 species have been identified in Peninsular Malaysia. The objective of this study is to provide a checklist of Utricularia species in western Sarawak. The method used was convenience sampling where surveys were conducted throughout Western Sarawak. In this study, a total of nine species of Utricularia was found in the western part of Sarawak (Kuching, Sri Aman, Serian, and Samarahan Divisions). Three species are common, namely U. bifida, U. minutissima, and U. aurea and one species is fairly common U. caerulea. Bako National Park has five species, U. minutissima, U. hirta, U. geoffrayi, U. subulata and U. uliginosa. Key words: Aquatic, Lentibulariaceae, terrestrial, Utricularia, Western Sarawak